WENTER SEBAGAI PEWARNA ALTERNATIF DALAM PEWARNAAN MEDIA PREPARAT JARINGAN BATANG DAN AKAR TUMBUHAN PLETEKAN (Ruellia sp.) DAN BELUNTAS (Pluchea indica) - NUR INDASARI, ICA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
This research aims to produce plant tissue preparation use wenter as the alternative dye in the plant tissue staining, describe absorbing each of the stem and root plant tissueÂ  component used wenter as the alternative dye. Development of the plant tissue preparation include analyze Standard competence and Basic competence in the XI grade of the Biology in SMA, making of pletekan (Ruellia sp.) and beluntas (Pluchea indica) plant tissue preparation used wenter as alternative dye with simple method, analyze plant tissue preparation to the plant anatomy lecturer, microtechnique lecturer and teacher of Biology in SMA. The research result show that each of pletekan and beluntas stem and root tissue have capability absorb wenter dye with different intensity. The plant tissue with thin cell wall, primary cell wall and life protoplasms like parenchyma, epidermis, floem and protoxylem (trakea) have high intensity to absorb the wenter dyes, the cell wall of that tisue look red colour. The tissue with secondary cell wall and lignified like schlerenchyma, metaxilem have low intensity to absorb wenter dye, the cell wall of that tissue look light yellow. Keywords: preparation media, plant tissue, alternative dye wenter